Effects of Topiramate on Language Functions - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Chonbuk National University Medical School, Korea, report the effects of topiramate on language functions in 38 newly diagnosed epileptic patients, mean age 10 +/- 2 years and 8 months.